A feasible technique for distinguishing the intersegmental plane by transbronchial injection of iron sucroseCentral MessagePerspective - Chengqiang Li, MD, PhD; Xianfei Zhang, MD, PhD; Xijia Feng, MD, PhD; Dingpei Han, MD, PhD; Jie Xiang, MD, PhD; Hecheng Li, MD, PhD (JTCVS Techniques)
Objectives: Pulmonary segmentectomy should be the standard surgical procedure for patients in certain clinical scenarios. However, detecting the intersegmental planes both on the pleural surface and within the lung parenchyma remains a challenge. We developed an intraoperative novel method for distinguishing intersegmental planes of the lung via transbronchial injection of iron sucrose (ClinicalTrials.gov number, NCT03516500). Methods: We first performed a bronchial injection of iron sucrose to identify the intersegmental plane of the porcine lung. Then, we conducted a prospective study to evaluate the safety and feasibility of the technique in 20 patients who underwent anatomic segmentectomy. Iron sucrose was injected into the bronchus of target pulmonary segments, and the intersegmental planes were divided with electrocautery or stapler. Results: The median injection of iron sucrose was 90 mL (range, 70-120 mL), and the median time from injection of iron sucrose to demarcation of intersegmental plane was 8 minutes (range, 3-25 minutes). Qualified identification of the intersegmental plane was observed in 17 cases (85%). The intersegmental plane could not be recognized in 3 cases. All patients experienced no complications related to iron sucrose injection or complications of Clavien–Dindo grade 3 or more. Conclusions: Transbronchial injection of iron sucrose is a simple, safe, and feasible approach to identify the intersegmental plane (NCT03516500).